KORELASI KARAKTERISTIK SOSIAL EKONOMI PETANI DENGAN TINGKAT ADOPSI COMBINE HARVESTER PADA USAHATANI PADI LAHAN PASANG SURUT DI KABUPATEN PULANG PISAU - Anto A; Sintha E. P. (Fakultas Pertanian Universitas Palangka Raya, 2020)
The study aimed to find out the correlation between the socio-economic characteristics of farmers with the adoption rate of combine harvester implementation in tidal swamplands farming system in Pulang Pisau Regency, Central Kalimantan Province. Pulang Pisau Regency was selected as a study site since the area is considered as one of the tidal swamplands rice-production centers in Central Kalimantan, and most of the farmers have used combine harvester. The data was collected by interview method to 52 selected farmer households based on simple random sampling. In order to determine the correlation, Rank Spearman (rs) test was used, and its significance was tested using t-test at the 0.05 significance level. It has been found that the adoption rate of combine harvester implementation was high. Moreover, some socio-economic characteristics related to the adoption rate were farmer experience, age, non-formal education, land area, and capital source. However, there was no correlation between formal education with the adoption rate of combine harvester implementation in tidal swamplands farming system in Pulang Pisau Regency